A Numerical Investigation on Behavior of Column Base Plates with Different Configurations - Shafieifar, Mohamadreza; Khonsari, Vahid (Salehan Institute of Higher Education, 2018)
Base plates are one of the most important types of connections in structures. Due to complicated steel-concrete interaction, simple assumptions of the stress distributions are usually employed for designing the connection. Simple assumptions of compressive stress distribution in concrete may accelerate the design procedure, but they may lead to overdesign results. In this study, six different types of base plates with different configuration were studied numerically using a commercial Finite Element (FE) software and the numerical model was calibrated with an experimental test. The models were subjected to a constant axial load and then a monotonic moment loading was applied. To investigate the effects of the axial load, several axial load level were considered for each configuration. As a result, moment-rotation curves of these base plates, including their rotational stiffness, in the absence and presence of the axial loads, were compared. Moreover, the stress distribution in the concrete was studied in the FE models. For all cases, the stress distribution in the concrete was semi-triangular with the maximum stress between the column flange and the edge of the plate. Based on numerical results, some concepts of simplified assumptions were proposed to find the stress distribution of the base plates. These assumptions are more realistic than current assumptions in structural specifications.